GQIcombi application to subdue glioma via differentiation therapy - Kolesnikova, Varvara; Revishchin, Alexander; Fab, Lika; Alekseeva, Anna; Ryabova, Anastasia; Pronin, Igor; Usachev, Dmitry Y.; Kopylov, Alexey; Pavlova, Galina (Frontiers in Oncology, 2024)
Current therapy protocols fail to cure high-grade gliomas and prevent recurrence. Therefore, novel approaches need to be developed. A re-programing of glioma cell fate is an alternative attractive way to stop tumor growth. The two-step protocol applies the antiproliferative GQ bi-(AID-1-T) and small molecule inducers with BDNF to trigger neural differentiation into terminally differentiated cells, and it is very effective on GB cell cultures. This original approach is a successful example of the “differentiation therapy”. To demonstrate a versatility of this approach, in this publication we have extended a palette of cell cultures to gliomas of II, III and IV Grades, and proved an applicability of that version of differential therapy for a variety of tumor cells. We have justified a sequential mode of adding of GQIcombi components to the glioma cells. We have shown a significant retardation of tumor growth after a direct injection of GQIcombi into the tumor in rat brain, model 101/8. Thus, the proposed strategy of influencing on cancer cell growth is applicable to be further translated for therapy use.